1993
DOI: 10.1677/joe.0.1370529
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide, but not pituitary adenylate cyclase-activating peptide, modulates the responsiveness of the gonadotroph to LHRH in man

Abstract: Vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating peptide (PACAP) are hypothalamic peptides sharing considerable sequence homology which are postulated to be hypophysiotrophic releasing factors. When infused into man, PACAP has no effect on anterior pituitary hormone levels, while VIP causes a significant increase in circulating prolactin concentrations. However, PACAP has recently been shown to augment the release of LH and FSH in response to LHRH in rat anterior pituitary cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…No adverse effects have been reported when given to humans with doses producing significant biologic effects. 16,17 In contrast to dexamethasone, PACAP may be safely given even in diabetic patients. PACAP might work in concert with other relevant neural and hormonal factors in feeding-induced insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…No adverse effects have been reported when given to humans with doses producing significant biologic effects. 16,17 In contrast to dexamethasone, PACAP may be safely given even in diabetic patients. PACAP might work in concert with other relevant neural and hormonal factors in feeding-induced insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The data we have regarding the influence of VIP on LH and FSH secretion are various. It is suggested that VIP could stimulate LH secretion [43][44][45]. The interactions between the pituitary thyroid axis and VIP have been very controversial in in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…Differential reduction in gonadotropin levels in VIP KO animals when compared with WT VIP action on pituitary LH and FSH secretion has long been controversial (Hammond et al 1993, Sawangjaroen et al 1997. LH and FSH could subsequently affect gonad development and functions, especially testicular steroidogenesis and spermatogenesis.…”
Section: Absence Of Vip Is Associated With Very Low Testosterone Levementioning
confidence: 99%